Numerical simulation of liquid/gas phase flow during mold filling - Tavakoli, Rohallah; Babaei, Reza; Varahram, Naser; Davami, Parviz (Computer methods in applied mechanics and engineering, 2006)
A numerical model for simulation of liquid/gas phase flow during mold filling is presented. The incompressible Navier–Stokes equations are discretized on a fixed Cartesian mesh with finite difference method. The fractional-step scheme is employed for enforcing incompressibility constraint. The free surface effects are calculated using the volume of fluid method based on the piecewise-linear interface reconstruction and split Lagrangian advection of volume fraction field. Adding limited compressibility to the gas phase led to improvement in convergence rate of Poisson equation solver (about 2-fold). This new concept permits simulation of two-phase incompressible free surface flow during mold filling, without using outflow boundary condition. Numerical results are presented for several test cases, which demonstrate validity, capability and performance of the proposed method in contrast with the traditional (fully incompressible) approach.